Literature Review : The Efforts To Strengthening of Micro, Small and Medium-Sized Enterprises (MSME) in Indonesia - Nafizha Trie Permata Sari; Andriani Kusumawati (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Poverty is a complex problem that is widespread in developing countries like Indonesia. MSMEs are seen as the engine of national economic progress, as they can engage large numbers of young people and the poor and thus increase productivity and community income for low-income groups. However, there are many problems with strengthening MSMEs, such as low-quality human resources, high raw material costs, intense business competition, lack of capital, lack of management skills, and a less conducive business climate. In the era of globalization, with a climate of intense business competition, one of the prerequisites for the survival of MSMEs is one of the capital requirements to increase the capacity and quality of the corresponding resources. Therefore, this article has been created to examine and examine what efforts can be made to strengthen MSMEs. This study uses qualitative research using a literature review method. We found that several programs that can be used as examples of MSME compatibility are: 1) Coaching programs in collaboration with the government, social agencies, and universities; 2) provide education and training to the public on business management and entrepreneurship; 3) develop digital technologies as a platform for MSMEs; 4) provide access to capital; 5) e-on learning;; 6) create policies that can encourage market-oriented MSMEs, 7) provide information to MSMEs, 8) build an innovative culture and 9) create entrepreneurship exhibitions and seminars to increase competitiveness.